Tackling a disease on a global scale, the Global Parkinson’s Genetics Program, GP2: a new generation of opportunities - Blauwendraat, Cornelis; Noyce, Alastair J.; Mata, Ignacio F.; Screven, Laurel A.; Solle, J.; Dumanis, Sonya B.; Riley, Ekemini A.; Perinan, Maria Teresa; Okubadejo, Njideka; Klein, Christine; Morris, Huw R.; Singleton, Andrew B.; et al. (Cell Press, Elsevier, 2025)
The need for more diversity in research is a widely recognized problem, especially in the genetics and genomics fields. While resolving this problem seems straightforward by recruiting and sequencing research participants from underrepresented populations, implementing an effort like this is complex operationally. Key considerations include ensuring equity, building capacity, and creating a sustainable research collective that works collaboratively to address local and global questions in research. Here, we provide a roadmap detailing how the Global Parkinson’s Genetics Program (GP2) is tackling the lack of diversity in Parkinson disease (PD) genetics research and also reflect on 5 years of progress. GP2 aims to be a global hub facilitating subject recruitment, sample collection, data generation, harmonization, and sharing. It also acts as a centralized target discovery hub for PD genetics worldwide. The underlying tenets of GP2 center on transparency, the democratization of data and discovery, training and career support, providing (or generating) actionable results, and creating a functional collective of PD researchers worldwide. GP2 is working with 275 research groups worldwide. There are data and samples from 265,000 subjects currently committed to the program as of May 2025. We discuss the lessons learned in this process and highlight what we view as the emerging opportunities that the program will aim to target over the next period.